Early Defoliation Techniques Enhance Yield Components, Grape and Wine Composition of cv. Trnjak (Vitis vinifera L.) in Dalmatian Hinterland Wine Region - Mucalo, Ana (Plants (Basel), 2021)
Defoliation and cluster thinning are of practical importance in a control of the grapevine source-sink balance, cluster architecture, microclimate and berry composition. Nevertheless, their effectiveness on wine composition is unexplored. In this work, the impacts of preflowering (T1), after berry set (T2), and veraison defoliation (T3) and cluster thinning (T4), on yield components, grape and wine composition of cv. Trnjak are given. Implemented techniques significantly reduced yield and affected grape and wine components in comparison to untreated control (C). Despite lowest number of clusters ensured by cluster thinning, defoliation at veraison had lowest yield. Defoliations improved cluster architecture parameters. Highest berry per se was in preflowering T1 and lowest at veraison T3 defoliation. Berries of T1 had lowest sugar content (19.47 °Brix) while T3 had highest (22.3 °Brix), and the reverse is seen in total acidity highest in T1 (6.12 g/L) and lowest in T3 (5.01 g/L). Wines of early defoliations (T1 and T2) had lowest alcohol and highest anthocyanin concentration. Both techniques applied at veraison produced wines with lower anthocyanins and flavonols than those obtained without any intervention (C). In conclusion, the early defoliations (T1 and T2) improve yield and wine composition of cv. Trnjak in the Mediterranean region of Croatia.